(untitled) (Journal of the Spanish Institute for Strategic Studies, 2021)
Book Review: KEPEL, Gilles. (2020). Getting out the chaos, The crisis in the mediterranean and the middle east. Translation by Elena M. Cano and Íñigo Sánchez-Paños. Gilles Kepel, Publisher: Alianza, 2021 Le prophète et la pandémie. Du Moyen-Orient au jihadisme d’atmosphère. Paris, Gallimard. ISBN 978-20-7292-312-8.